Еxpression of cerebral endothelial NLRP3 inflammasome in viral inflammation in vitro - A. B. Salmina; E. B. Boytsova; A. V. Morgun; Yu. A. Panina; Ya. V. Gorina; N. V. Pisareva; M. Noda; I. A. Kutishcheva; G. P. Martynova (Бюллетень сибирской медицины)
The goal is to study the effects of pro-inflammatory agents on the expression of NLRP3 and the structural integrity of cerebral microvessel endothelial cells in vitro.Materials and methods. The study was conducted on a culture of cerebral endothelial cells. The cells were isolated from Wistar rat brains. Polyinosinic-polycytidylic acid (RolyI: C) – 20 µg / ml was added to cerebral microvessel endothelial cells. In another series of experiments, cells incubated with cerebrospinal fluid (CSF) obtained from patients with enteroviral meningitis (100 µl) were used as a comparison group. CSF was standardized for protein concentration by the Lowry method. The protein concentration was 1 µg / ml. As a control group, cerebral endothelial cells have been cultured in a standard medium. We used the culture insert for 12-well plates. After 24 and 72 h of culturing, we measured transendothelial electrical resistance (TEER) in the endothelial layer. Expression of NLRP3 inflammasomes was assessed with immunocytochemistry 24 hrs from the beginning of cell culture. We used double indirect immunoenzymatic staining method according to the manufacturer’s protocol. Primary antibodies to NLRP3 (Abcam, USA, ab51952) in 1: 100 dilution, secondary antibodies labeled with Alexa Fluor 488 (Abcam, USA, ab150117) in dilution 1: 200 have been applied. Visualization was performed by confocal laser microscopy microscope Olympus FV10i (Olympus, Japan).Results. TEER decreased in PolyI:C and CSF-treated cells after 24 hr from the beginning of incubation. After 72 hours, TEER was significantly lower in these groups compare to the control one. NLRP3 expression was maximal in the cells treated with CSF. After incubation of the cells with PolyI:C, NLRP3 expression in cerebral endothelial cells was elevated compare to the control group, but did not reached the level seen in CSF-treated cells.Conclusion. PolyI:C and CSF obtained from the patients with viral meningitis induce disruption of cerebral microvessels endothelial layer integrity with the corresponding rise in NLRP3 expression in the cells, thereby suggesting mechanism of blood-brain barrier impairment in neuroinfection.